2013
DOI: 10.1007/s13277-013-0799-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between NQO1 C609T polymorphism and bladder cancer susceptibility: a systemic review and meta-analysis

Abstract: There is growing evidence for the important roles of genetic factors in the host's susceptibility to bladder cancer. NAD(P)H:quinone oxidoreductase 1 (NQO1) is a cytosolic enzyme that catalyzes the two-electron reduction of quinoid compounds into hydroquinones. Since the NQO1 C609T polymorphism is linked to enzymatic activity of NQO1, it has also been hypothesized that NQO1 C609T polymorphism may affect the host's susceptibility to bladder cancer by modifying the exposure to carcinogens. There were many studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Furthermore, great numbers of association studies have been conducted to explore the relationship between NQO1 Pro187Ser or SULT1A1 Arg213His polymorphism and the risk of BC. Moreover, the increased effects of NQO1 Pro187Ser or SULT1A1 Arg213His polymorphism on the risk of various cancers including BC have been clarified by the previous meta-analyses [14][15][16][17][18][19][20]. Importantly, a certain amount of the original study has not only investigated the individual effect of NQO1 Pro187Ser or SULT1A1 Arg213His on the risk of BC but has also examined the genetic effect of NQO1 Pro187Ser or SULT1A1 Arg213His modified by smoking on BC risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, great numbers of association studies have been conducted to explore the relationship between NQO1 Pro187Ser or SULT1A1 Arg213His polymorphism and the risk of BC. Moreover, the increased effects of NQO1 Pro187Ser or SULT1A1 Arg213His polymorphism on the risk of various cancers including BC have been clarified by the previous meta-analyses [14][15][16][17][18][19][20]. Importantly, a certain amount of the original study has not only investigated the individual effect of NQO1 Pro187Ser or SULT1A1 Arg213His on the risk of BC but has also examined the genetic effect of NQO1 Pro187Ser or SULT1A1 Arg213His modified by smoking on BC risk.…”
Section: Introductionmentioning
confidence: 99%
“…The study carried out by Zhang et al [ 43 ], including nine publications with 2661 cases and 2738 controls, observed no association under all genetics models. Similarly, Gong et al also failed to detect any association, while analyzing 11 studies with 2937 cases and 3008 controls [ 44 ]. A meta-analysis by Lajin et al [ 45 ], pertaining to all types of cancer, observed a significantly increased overall cancer risk with variant Ser/Ser genotype, as compared to the homozygous wild type (Pro/Pro).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence for the important roles of genetic factors in the host’s susceptibility to bladder cancer [3032]. Currently, there are several genetic polymorphisms which have been identified as risk factors of bladder cancer, such as cyclin D1 (CCND1) G870A polymorphism [10] and NQO1 C609T polymorphism [33]. There were a series of studies that have looked into the association between the MMP polymorphisms and bladder cancer susceptibility; however, the results obtained were inconsistent or controversial [13, 19–23].…”
Section: Discussionmentioning
confidence: 99%